Productivity reimagined : shattering performance myths to achieve sustainable growth - Stoller, Jacob (John Wiley & Sons, Inc., 2025)
"Productivity Reimagined shows how seven deeply entrenched myths about business management sabotage productivity, and then outlines a clear path forward for sustainable growth. Evidence is drawn from Toyota and a select group of other companies that have successfully countered these myths, supplemented by expert insights on psychology, systems theory, and technology. The book concludes with an urgent call for businesses to improve productivity in order to address the pressing global issues of our time"-- Provided by publisher.
Keywords: Industrial productivity.; Labor productivity.; Production (Economic theory); Sustainable development.; elektronické knihy; electronic books